Konseling Islam: Studi terhadap Posisi dan Peta Keilmuan - Tajiri, Hajir (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2012)
Islamic counseling positions are in the debate between education, psychology and dakwah. All of them have a chance to develop Islamic counseling further. Educational counseling regards as one of the approaches in education and has had a very long history. Meanwhile counseling psychology claims as part of the work is the application of psychology and psychologists called counseling psychologists. In the middle of the debate, in Islamic science, it is dakwah science has been developed what is called irsyad and formula is not much different from counseling, just because it is in dakwah domain, it is shades of religious activity. Dakwah looked more entitled to counseling skills, because in dakwah, counseling activities that have been carried out by Muslims and fused with the dakwah activities.